(3HTQi GddHjH HPcQ GdMHjHs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s
(3ChdgG (B:s
(3HYO MeO Gddg Ydi Lejd GdGdBQGA adeG QhjJ bUjOI cYH Hf RgjQ (B((3HGfJ SYGO(B) (3jeOM HgG SjO GdeQSdjf BKQJ GdJHQc HgPG GdSdhc Ke hLOJ HY Pdc ef CSeGFg Ydjg GdSdGe afXeJ bUjOI ajgG s
(3BNQgG (B:s
(3PcQ CMGOjK JJYdb HGdeMHI ai Gddg , heMHI Gddg JYGdi QShdg Udi Gddg Ydjg hSde BNQg hGdMeO ddg s
(3YdjgG bQGAI SfI (B729s
(3hGdfSNI efbhdI Yf fSNI GdeUfa hYdjgG NW CHj MLQ GdYSbdGfis
(3hHgG HYV GdVHWs
(3hHiNQgG SeGYGJ Vefg eG fXeg ef bUGFO ai eOM GdfHi U eQJHI Ydi MQha GdeYLe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
Keywords: (3GdCOHs